A few nifty tips for conducting scientific research - Lupei Zhu (Earthquake Science)
Scientific research is a journey into an uncharted territory. Researchers need to have the big picture for navigation and at the same time be detail-oriented, as details make a difference. Here I offer a few tips for conducting research that I summarized based on my 30+ years of research experience.